3-Dimensional implant planning in prosthetic dentistry and surgical guides - Abdullah Oğuz Hamiş; Oğuz Ozan; Serhat Ramoğlu (Gazi University, 2016)
In implant dentistry, technological inventions are now being utilized in order to achieve better treatment results; thus failures associated with conventional surgical techniques are reduced. With the use of 3-dimensional computer-assisted planning, the density and the width of bone, and anatomic landmarks can be observed in detail and also a 3-dimensional model of the bone tissue can be constructed. By using contemporary radiological and surgical guides, fabrication of superior quality implant-supported restorations is possible. In this review, information regarding planning methods to get better prosthetic results in dental implant treatments has been given. Also, the accuracy of these methods has been evaluated in the light of the current dental literature.